Proposals for Development Programme for the Year 1971-72 Part I Descriptive Chapters Government of Gujarat - Planning Commission (Planning Commission, 1970)
Priorities envisaged in the Annual Plan 1971-72 are more or less the same as adopted in the State’s Fourth Five Year Plan. Agriculture has been given the highest priority. For agricultural programmes together with irrigation, cooperation, community development and panchayats including provisions for these programmes included within the earmarked outlays for the programme of selected district level schemes, an outlay of Rs. 38.23 crores, has been earmarked for the year 1971-72, which is about 41.6 per cent of the total outlay of Rs. 91.98 crores. In addition, an outlay of Rs. 145 lakhs is proposed for rural electrification which will also help increase the agricultural production.
Government of Gujarat, General Administration Department